Population structure, inbreeding and admixture in local cattle populations managed by community‐based breeding programs in Burkina Faso - Ouédraogo, D.; Ouédraogo-Koné, S.; Yougbaré, B.; Soudré, A.; Zoma‑Traoré, B.; Mészáros, Gábor; Khayatzadeh, N.; Traoré, A.; Sanou, M.; Okeyo Mwai, Ally; Wurzinger, Maria; Burger, P.A.; et al. (Wiley, 2021)
High‐throughput genomic markers provide an opportunity to assess important indicators of genetic diversity for populations managed in livestock breeding programs. While well‐structured breeding programs are common in developed countries, in developing country situations, especially in West Africa, on‐farm performance and pedigree recordings are rare, and thus, genomic markers provide insights to the levels of genetic diversity, inbreeding and introgression by other breeds. In this study, we analysed key population parameters such as population structure, admixture and levels of inbreeding in three neighbouring populations of African taurine and taurine × Zebu crosses managed by community‐based breeding programs in the South‐West of Burkina Faso. The three populations were pure Baoulé (called Lobi locally) in sedentary production systems, Baoulé x Zebu crossbreds in sedentary systems and Zebu × Baoulé crossbreds in transhumant production systems, respectively. The total sample analysed included 631 animals and 38,207 single nucleotide polymorphisms after quality control. Results of principal component and admixture analyses confirmed the genetic background of two distinct ancestral populations (taurine and zebuine) and levels of admixture in all three breeding populations, including the presumably pure Baoulé group of animals. Inbreeding levels were moderate, compared to European dairy and beef cattle populations and higher than those of Brazilian Nellore cattle. Very few animals with inbreeding levels indicating parent–offspring or full sib mating were observed, and inbreeding levels indicating half sib mating were also rare. For the management of breeding populations, farmers were advised to exchange best young bulls. The crossbreeding levels of presumably pure Baoulé animals are of concern to the breeding program due to the high level of endangerment of pure African taurine cattle populations across West Africa. Future rounds of bull selection in the community‐based breeding program will make use of genomic information about admixture levels.